1985
DOI: 10.1080/03014223.1985.10428308
|View full text |Cite
|
Sign up to set email alerts
|

Status and foraging in New Zealand honeyeaters

Abstract: Aggression is a common feature of sociality among nectar-feeding birds, and these have been used to consider many aspects of ecological theory, for example community structure, foraging patterns, social organisation and plant-pollinator systems.Knowledge of aggression among and within New Zealand's honeyeater species is reviewed. Additional information on the importance of various asymmetric cues as learned predictors of status is considered. High-status individuals appear to gain access to nectar in all situa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
(17 reference statements)
1
14
0
Order By: Relevance
“…Females rise in status and approach that of their mates during the breeding season. Similar correlations have been reported in bellbirds (Craig & Douglas 1986;Craig 1985). Downloaded by [University Of Pittsburgh] at 18:00 18 November 2014 Differences in status may explain variations in movement among individual tui.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Females rise in status and approach that of their mates during the breeding season. Similar correlations have been reported in bellbirds (Craig & Douglas 1986;Craig 1985). Downloaded by [University Of Pittsburgh] at 18:00 18 November 2014 Differences in status may explain variations in movement among individual tui.…”
Section: Discussionsupporting
confidence: 75%
“…Zealand's three honeyeaters, the tui iProsthemadera novaeseelandiae) is the largest (Craiget al 1981 b) and the most dominant (Craig 1985). As the largest, its energy demands per individual are highest; but as the most dominant, its access to the best quality resources is assured.…”
Section: Introductionmentioning
confidence: 97%
“…This is also in accordance with several studies using a wide range of experimental approaches that have shown birds to be more efficient pollinators than insects (Bertin 1982; Ramsey 1988; Stewart & Craig 1989; Vaughton 1996; Anderson 1997). Among the factors that help to explain the success of birds in effecting fruit and seed set are their relative abundance, body size, foraging patterns and status (Craig 1985; Stewart & Craig 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Quite apart from pollinator abundance, factors such as foraging patterns, flight distances, body size and social hierarchy of pollinators may influence the mating system (Waser, 1982;Craig, 1985;Stewart and Craig, 1989;Karron et al, 1995). In some insect-pollinated plants, for example, the high interpopulation variation in outcrossing rates can be largely attributed to the behavior of pollinators (Schemske and Lande, 1985).…”
Section: Discussionmentioning
confidence: 99%